Board compensation and investment efficiency - Martin Gregor; Beatrice Michaeli (Charles University in Prague, Institute of Economic Studies (IES), 2024)
In their role as initiators of new business projects, CEOs have an advantage over access to and control over project-related information. This exacerbates pre-existing agency frictions and may lead to investment inefficiencies. To counteract this challenge, incentive compensation for corporate boards (responsible for approving major projects) emerges as a critical governance tool. Our study demonstrates that the optimal compensation design requires strategically allocating a liability burden between CEOs and boards. When this burden is shifted onto the boards, shareholders reduce management rents, albeit at the expense of residual inefficiency. Our findings thus highlight that shareholders' tolerance for investment inefficiencies may be rooted in optimal compensation. We predict that contracts tolerating excessive investments are optimal under conditions of low labor market value for CEOs, severe CEO empire-building, and attractive outside options for directors. Because of structural changes associated with the reallocation of financial incentives, the non-financial characteristics of CEOs and boards may impact investment efficiency, information quality, project profits, and management rents in a non-monotonic manner.
Keywords: D83; D86; G30; G31; G34; 330; Board monitoring; director compensation; investment inefficiency